Chemical Composition of Essential Oils from Thymus vulgaris, Cymbopogon citratus, and Rosmarinus officinalis, and Their Effects on the HIV‐1 Tat Protein Function. Issue 2 (31st January 2018) - Feriotto, Giordana; Marchetti, Nicola; Costa, Valentina; Beninati, Simone; Tagliati, Federico; Mischiati, Carlo
Abstract : New drugs would be beneficial to fight resistant HIV strains, in particular those capable of interfering with essential viral functions other than those targeted by highly active antiretroviral therapy drugs. Despite the central role played by Tat protein in HIV transcription, a search for vegetable extracts able to hamper this important viral function was never carried out. In this work, we evaluated the chemical composition and possible interference of essential oil from Thymus vulgaris, Cananga odorata, Cymbopogon citratus, and Rosmarinus officinalis with the Tat/TAR‐RNA interaction and with Tat‐induced HIV‐1 LTR transcription. GC/MS Analysis demonstrated the biodiversity of herbal species translated into essential oils composed of different blends of terpenes. In all of them, 4 – 6 constituents represent from 81.63% to 95.19% of the total terpenes. Essential oils of Thymus vulgaris, Cymbopogon citratus, and Rosmarinus officinalis were active in interfering with Tat functions, encouraging further studies to identify single terpenes responsible for the antiviral activity. In view of the quite different composition of these essential oils, we concluded that their interference on Tat function depends on specific terpene or a characteristic blend. Abstract :